The Impact of Cognitive Biases on Corporate Decision-Making: Analysis and Mitigation Strategies - He Ruoyan (SHS Web of Conferences)
In the business world, decisions are like the heartbeat of an organisation. They determine the strategy a company follows, influence its financial results, and shape its unique company culture. This paper analyzes three cognitive biases-confirmation bias, fundamental attribution error, and conformity bias-and explores their effects and consequences on corporate decision-making. These biases can lead to misjudgments by senior management in areas such as employee evaluation, hiring decisions, team collaboration, and customer relationship management. Additionally, they may foster a culture of flattery within the organization, which can negatively affect overall innovation and growth. By implementing strategies such as diverse team-building, data-driven decision-making, and fostering a culture of open feedback, companies can effectively mitigate the adverse effects of these cognitive biases on decision-making. While this study does not cover all biases that affect corporate decision-making, it offers a new perspective for understanding and improving the decision-making process, providing valuable insights for future research and practice.